2022
DOI: 10.1088/1478-3975/ac8c15
|View full text |Cite
|
Sign up to set email alerts
|

A compressed logistic equation on bacteria growth: inferring time-dependent growth rate

Abstract: We propose a compressed logistic model for bacterial growth by invoking a time-dependent rate instead of the intrinsic growth rate (constant), which was adopted in traditional logistic models. The new model may have a better physiological basis than the traditional ones, and it replicates experimental observations, such as the case example for E. coli, Salmonella, and Staphylococcus aureus. Stochastic colonial growth at a different rate may have a fractal-like nature, which should be an origin of the time-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Urban wastewater represents one of the main sources of contamination of interconnected water bodies of many types, such as rivers, lakes, ponds, wetlands and reservoirs (Pinto & Shimakawa, 2022;Sekharan et al, 2022), and its discharge (even treated) to water bodies could increase the levels of these emerging pollutants in the environment, disrupting the ecological balance (Calero-Cáceres et al, 2022;Villa-Achupallas et al, 2018). Although several studies have shown that urban discharges promote the persistence and spread of antibiotic resistance, limited information is available from developing countries (Arcentales-Ríos et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Urban wastewater represents one of the main sources of contamination of interconnected water bodies of many types, such as rivers, lakes, ponds, wetlands and reservoirs (Pinto & Shimakawa, 2022;Sekharan et al, 2022), and its discharge (even treated) to water bodies could increase the levels of these emerging pollutants in the environment, disrupting the ecological balance (Calero-Cáceres et al, 2022;Villa-Achupallas et al, 2018). Although several studies have shown that urban discharges promote the persistence and spread of antibiotic resistance, limited information is available from developing countries (Arcentales-Ríos et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several growth models are found in the literature, such as the models of Gompertz (1825); Richards (1959); Stannard et al, (1985); Polese et al, (2011); Bhatia et al, (Bhatia et al, 2011); Erbas et al, (2014); Kim et al, (Kim et al, 2018) and the logistic model Razanamahandry et al, (Razanamahandry et al, 2018); Chen et al, (2020) and others by Choi & Seo (2018); Sreenivas et al, (2020); Łobacz et al, (2022). Models are abstractions of reality; in fact, they can all be considered essential to capture different scales of a phenomenon and to better understand the dynamics of an ecosystem (Hadi, 2023;Pinto & Shimakawa, 2022;A Succurro et al, 2017;Antonella Succurro & Ebenhöh, 2018). On the one hand, there are models with deterministic approaches (based on differential equations and stoichiometric models with constraints) and, on the other hand, models with stochastic approaches (associated with a cumulative distribution function and a probability density function).…”
Section: Theoretical Referentialmentioning
confidence: 99%
See 2 more Smart Citations
“…A Logistic model is a nonlinear model, which can describe the decreasing or increasing trend of dependent variable with the independent variable. The Logistic model is expressed as follows [ 31 ] where is the weight loss for ‘Red Globe’ and ‘Wink’; is the storage time, is the baseline, are the constants of the equations with the storage time.…”
Section: Methodsmentioning
confidence: 99%